2018
DOI: 10.1186/s12882-018-0871-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the physical and psychosocial outcomes after living kidney donation - a multicenter cohort study (SoLKiD - Safety of Living Kidney Donors)

Abstract: BackgroundOver the last years, living kidney donation (LKD) has been established for patients with endstage renal failure as an alternative to post mortem donation, which is limited by organ scarcity and long lasting waiting periods. From an ethical perspective, the increase in LKD requires that donors’ physical, psychological, and social harm has to be minimized as much as possible and the risk should not exceed the generally expected consequences of nephrectomy. Despite of numerous, mainly retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Interestingly, the correlation between GDF15 and eGFR in the group of LD was not preserved in opposite to recipients, hinting towards a different mechanism of GDF15 activation in LD. This is an arousing aspect since it was shown that patients with chronic fatigue syndrome, which has been linked to LD, display higher GDF15 levels than healthy controls [30,31]. Interestingly, healthy controls had GDF15 values comparable to LD values before surgery, while patients with fatigue had comparable values to LD one year after KD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the correlation between GDF15 and eGFR in the group of LD was not preserved in opposite to recipients, hinting towards a different mechanism of GDF15 activation in LD. This is an arousing aspect since it was shown that patients with chronic fatigue syndrome, which has been linked to LD, display higher GDF15 levels than healthy controls [30,31]. Interestingly, healthy controls had GDF15 values comparable to LD values before surgery, while patients with fatigue had comparable values to LD one year after KD.…”
Section: Discussionmentioning
confidence: 99%
“…This is consonant with the quality of life described after donation in the long-term follow-up of living kidney donors. 43 While some studies found that the rate of hypertension after unilateral nephrectomy to be as high as 25-74.5%, others failed to show any increase in BP after surgery. The frequency of hypertension in the present donor population was lower than that in the healthy adult population of Egypt (22% versus 26%); this is not unexpected, because the donors were positively selected for a normal BP.…”
Section: Long Term Riskmentioning
confidence: 99%
“…Das Deutsche Lebendspende Register SOLKID-GNR (Safety of the Living Kidney Donor -The German National Register) wurde als Nachfolgeprojekt der in Münster initiierten SoLKiD Studie [13] als interdisziplinäres Register von drei Transplantationszentren (Münster, Heidelberg, Hamburg, jetzt Mainz) im Rahmen des BMBF (Bun-desministerium für Bildung und Forschung) Calls "Modellhafte Register -Konzeptentwicklungsphase" (Förderkennzeichen: 01GY1725) beantragt. Das BMBF fördert seit dem 1.…”
Section: Registerstrukturunclassified